Tests of Integrin Transmembrane Domain Homo-oligomerization during Integrin Ligand Binding and Signaling - Wang, Wei (American Society for Biochemistry and Molecular Biology, 2011)
Integrin transmembrane (TM) and/or cytoplasmic domains play a critical role in integrin bidirectional signaling. Although it has been shown that TM and/or cytoplasmic α and β domains associate in the resting state and separation of these domains is required for both inside-out and outside-in signaling, the role of TM homomeric association remains elusive. Formation of TM homo-oligomers was observed in micelles and bacterial membranes previously, and it has been proposed that homomeric association is important for integrin activation and clustering. This study addresses whether integrin TM domains form homo-oligomers in mammalian cell membranes using cysteine scanning mutagenesis. Our results show that TM homomeric interaction does not occur before or after soluble ligand binding or during inside-out activation. In addition, even though the cysteine mutants and the heterodimeric disulfide-bounded mutant could form clusters after adhering to immobilized ligand, the integrin TM domains do not form homo-oligomers, suggesting that integrin TM homomeric association is not critical for integrin clustering or outside-in signaling. Therefore, integrin TM homo-oligomerization is not required for integrin activation, ligand binding, or signaling.